Strategi Komunikasi Dakwah Akun Instagram @IpmJogja - Insani Dwi Nurhayati; Imam Suprabowo (LP2M IAI Muhammadiyah Sinjai, 2023)
This research aims to find out the da’wah communication strategy done by @ipmjogja whose followers are the most compared to other regional offices in the Special Region of Yogyakarta and the results obtained by @ipmjogja in communicating its da’wah via social media of Instagram. Based on the problem formulation and research objectives, it is hoped that the research can be a useful reference to other leaders or the public who want to use the same communication strategy through Instagram media. The research used a qualitative approach in which the obtained data are stated in a state that should or should be, as it is which does not come to a change of all forms, symbols, or numbers. The researcher employed a descriptive qualitative approach which means that the research is intended to accurately explain phenomena or characteristics of certain individuals, circumstances, or groups. Based on the interview conducted with 3 informants and the observation of the @ipmjogja Instagram account conducted online via WhatsApp text and face-to-face, the findings are; In the data collection, the regional leadership of the Muhammadiyah Student Association of Yogyakarta collected facts and data about the reason for the popularity of Instagram as the most widely used social media. It is possible for the @ipmjogja account to have the most followers because this account has been the most fully aware media compared to other regional leaders. In addition, this account is also eager to collect information about the most updated topic discussed by the community, especially students, which is used as a content concept. Planning: There are several things that must be considered regarding the content that will be broadcasted, such as credible content. The information that will be conveyed must be in accordance with the target who are students, and the harmony between content. After getting credible and appropriate data, the content creator or designer will create content by paying attention to the harmony of colors and fonts in the previous content. Communication (Communicating data): They have a workflow where content planners and designers must submit the results to the person in charge before uploading them to Instagram. If anything is not fulfilled, it will be returned and revised. Evaluation (Evaluating if the goals are achieved or not), the strategy is achieved when the followers realize that they get a lot of useful information from the @ipmjogja Instagram account. Second, the results achieved by the @ipmjogja account in preaching on social media of Instagram are; the da'wah information is delivered faster and gets more attention than other regional leaders in the Special Region of Yogyakarta